Daerah Rawan Genangan Rob di Wilayah Semarang - Ramadhany, Apriliawan Setiya; Subardjo, Petrus; Suryo, Agus Anugroho Dwi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
This study aims to determine the broad tidal inundation during the study and the level of vulnerability to tidal inundation that occurred in Semarang. Benefit of this study is to provide information about the areas that are prone to rob puddles and how much the extent area of rob that occur on the mainland of Semarang. There are five levels of vulnerability classes in Semarang area, starting from the very vulnerable class 625, 45 Ha, Ha 1418.92 prone, somewhat prone to 4807, 52 Ha, safe 1325, 57 Ha, very safe and 1157.54 ha with a total area of 9334.46 Ha. The spread of inundation rob Semarang region in 2011 is amounted to 1538.8 hectares. The North Region of Semarang is the most affected by tidal inundation, up to 508.28 hectares are affected. The second largest is at Genuk District with a total area of 377.68 hectares puddle. Extensive tidal inundation of 257.20 hectares located in the District Tugu furthermore, tidal inundation area of 237.19 hectares located in the District of West Semarang. The rest are spread in Semarang District Central, South and Gayamsari Semarang.